Mahasiswa KKN UNRI Ikut Berpartisipasi Turnamen Bola Voli Antar Kecamatan dalam Rangka Hari Jadi Pondok Gelugur yang Ke-76 - Nur Faradiba Amalia Sholeha; Amriz Maywanda Habib; Zahra Nur Adilla; Afni Fuji Astuti; Khalida Kirani; Habib Irza; Aditia Sembiring; Bayu Aji Pranata; Rut Desria Sitanggang; Ester Lamtama Frida Silaban (Yayasan Daarul Huda Kruengmane, 2026)
In celebration of the 76th anniversary of Pondok Gelugur Village, Universitas Riau (Unri) community service (KKN) students actively participated in an Inter-District Volleyball Tournament alongside local youth and residents. The students' participation aimed not only to enliven the competition, but also to serve as a means of social integration to strengthen ties and foster a sense of togetherness with the community. The presence of the Unri KKN team received warm appreciation from the village government and residents, as it brought positive energy and demonstrated a tangible form of community engagement beyond formal academic programs.